2012
DOI: 10.7126/cdj.2012.1092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of thermal stresses on tooth-colored posts, cores and tooth structures by finite element analysis

Abstract: Objectives: The aims of this study were to analyze the influence of cold heat flow in all ceramic crown material, composite core, zirconium and glass fiber reinforced composite post materials, resin based luting cement and root dentin; and to compare these two tooth-colored post systems about their temperature and thermal stress distributions. <br />Materials and Methods: A 3-dimesional finite element model of maxillary left canine tooth was constructed. All ceramic crown, composite core, tooth dentin, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…It can be also concluded from the results that titanium post produced the highest stress followed by the group restored by fiber post. The outcomes of this study corroborate earlier findings which have revealed that metallic post yields larger stresses than metal-free posts 32,41,64) . On the other hand, in PEEK post the resulted stresses were homogeneously distributed over larger areas resulting in the least stress concentration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It can be also concluded from the results that titanium post produced the highest stress followed by the group restored by fiber post. The outcomes of this study corroborate earlier findings which have revealed that metallic post yields larger stresses than metal-free posts 32,41,64) . On the other hand, in PEEK post the resulted stresses were homogeneously distributed over larger areas resulting in the least stress concentration.…”
Section: Discussionsupporting
confidence: 91%
“…The materials used in the present simulation were assumed to be homogenous, isotropic and linear elastic. Since the analysis was performed for two purposes, mechanical and thermal properties of all materials (Young's modulus, Poisson's ratio, density, specific heat, thermal expansion coefficient, and thermal conductivity) were defined for every part of the assembly according to previous literature data 41,[60][61][62][63][64] , and have been presented in Table 1.…”
Section: D Modeling Of Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-fabricated fiber post systems have been widely accepted as a treatment option offering not only esthetics and function [1][2][3][4], but also saving time and reducing costs [5][6][7]. Fiber posts consist of fibers including carbon, glass, quartz and zircon in a resin matrix with a silane coupling agent binding the fibers and matrix together [3].…”
Section: Introductionmentioning
confidence: 99%